Morphological and molecular analyses for the characterization of Aspalanthus linearis (Fabaceae: rooibos) - Potts, Alistair (Department of Biological Sciences, 2017)
I investigated the infraspecific diversity among individuals of Aspalathus linearis from five localities in the Cederberg Fynbos region using morphological traits and two DNA- based methods: inter-simple sequence repeats (ISSR) and a plastid marker. A principle component analysis (PCA) based on seven morphological variables grouped the samples into three different growth forms, specifically an erect-form, a prostrate-form and a shrub-form. The genetic variability of four plastid markers and one nuclear marker was determined for seven individuals selected from the populations. The trnL'UAAF-trnFGAA plastid marker was used to amplify the remaining samples and revealed four haplotypes, with a basal haplotype fixed in both the prostrate form and a single population of the erect form, a unique haplotype fixed in the shrub form, and a mix of two other haplotypes in the remaining erect forms. The congruence between haplotypes and regeneration strategy suggests a longstanding pattern of restricted gene flow. However, a small sample size associated with the plastid marker data limits or reduces the certainty of these findings.